Introduction of anaerobic dechlorinating bacteria into soil slurry microcosms and nested-PCR monitoring. - el Fantroussi, S (1997)
Desulfomonile tiedjei and Desulfitobacterium dehalogenans were chosen as model bacteria to demonstrate the introduction of an anaerobic microbia reductive dechlorination activity into nonsterile soil slurry microcosms by inoculation. De novo 3-chlorobenzoate dechlorination activity was established with the bacterium D. tiedjei in microcosms normally devoid of this dechlorination capacity. The addition of D. tiedjei to microcosms supplemented with 20 mM pyruvate as the cosubstrate resulted in total biotransformation of 1.5 mM 3-chlorobenzoate within 7 days. The introduction of the bacterium Desulfitobacterium dehalogenans into nonsterile microcosms resulted in a shortening of the period required for dechlorination activity to be established. In microcosms inoculated with Desulfitobacterium dehalogenans, total degradation of 6 mM 3-chloro-4-hydroxy phenoxyacetic acid (3-Cl-4-OHPA) was observed after 4 days in contrast to the result in noninoculated microcosms, where the total degradation of 3-Cl-4-OHPA by indigenous microorganisms was observed after 11 days. Both externally introduced bacterial strains were detected in soil slurry microcosms by a nested-PCR methodology.